Child cognitive development based on the maternal education - Inas Hanifah; Fitri Oviyanti; Muhtarom (Atfaluna: Journal of Islamic Early Childhood Education, 2022)
This quantitative research explores the differences in early childhood cognitive development levels based on the mother’s educational background. Using observation-based performance assessments, measure children’s cognitive development through 3 aspects: child social interaction, understanding of symbols, and reasoning involving samples. This study involved 30 children aged 5-6 years divided into two groups. The first group was children who had mothers with university-level education, while the other group was children with high school-level education. The collected data were analyzed to describe the demographic char samples’ demographic characteristics using an independent t-test to measure cognitive differences between the two groups of children. Significantly the educated mother results showed differences in cognitive development between the groups. Children with highly educated mothers have better cognitive abilities than children with mothers from a lower level of education. This research has implications for the importance of parental education to optimize children’s cognitive development.